Investigation of anti-galectin-8 levels in patients with multiple sclerosis: A consort-clinical study. Issue 1 (6th January 2023) - Cinkir, Ufuk; Bir, Levent Sinan; Tekin, Selma; Karagulmez, Ahmet Magrur; Avci Cicek, Esin; Senol, Hande
Abstract : Background: Galectins are a family of endogenous mammalian lectins involved in pathogen recognition, killing, and facilitating the entry of microbial pathogens and parasites into the host. They are the intermediators that decipher glycan-containing information about the host immune cells and microbial structures to modulate signaling events that cause cellular proliferation, chemotaxis, cytokine secretion, and cell-to-cell communication. They have subgroups that take place in different roles in the immune system. The effect of galectin-8 on multiple sclerosis disease (MS) has been studied in the literature, but the results seemed unclear. In this study, we aimed to determine anti-galectin-8 (anti-Gal-8) levels in MS and their potential use as biomarkers. Methods: In this experimental study, 45 MS patients diagnosed according to McDonald criteria were included in the patient group. The healthy control group contained 45 people without MS diagnosis and any risk factors. Demographic data, height, weight, body mass index, blood glucose, thyroid-stimulating hormone, alanine transaminase, aspartate transaminase, creatinine, low-density lipoprotein, anti-Gal-8 levels, the prevalence of hypertension, diabetes mellitus and coronary artery disease were recorded. In addition, the expanded disability status scale and disease duration were evaluated in the patient group. Data were presented as mean ± standard deviations. Results: The mean blood anti-galectin-8 value of the patient group was 4.84 ± 4.53 ng/mL, while it was 4.67 ± 3.40 ng/mL in the control group, and the difference in these values was found statistically insignificant ( P > .05). Moreover, body mass index, glucose, alanine transaminase, aspartate transaminase, thyroid-stimulating hormone, and low-density lipoprotein levels were also statistically insignificant ( P > .05). Conclusion: This study examined anti-Gal-8 levels in MS patients. The relationship between MS and galectin-8 and anti-Gal-8 levels in patients needs further clarification. As a result, the study's results could help elucidate the pathogenesis of MS and give more evidence for diagnosis.